2021
DOI: 10.1108/jerer-12-2020-0059
|View full text |Cite
|
Sign up to set email alerts
|

Cyclicity of real estate-related trends: topic modelling and sentiment analysis on German real estate news

Abstract: PurposeThe purpose of this paper is to identify and analyse the news coverage and sentiment of real estate-related trends in Germany. Trends are considered as being stable and long-term. If the news coverage and sentiment of trends underlie cyclicity, this could impact investors’ behaviour. For instance, in the case of increased reporting on sustainability issues, investors may be inclined to invest more in sustainable buildings, assuming that this is of growing importance to their clients. Hence, investors co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Therefore, we have performed an automated web data extraction method: web scraping. Individual scripts were developed to scrape the warehouse information from the Html file and assemble one dataset for each metropolitan area (Ge et al, 2021;Gharahighehi et al, 2021;Jiao et al, 2021;Luo and He, 2021;Pineda-Jaramillo and Pineda-Jaramillo, 2021;Ploessl et al, 2021). This method was mainly composed of seven steps for this paper: (i) find the URL where the data is published; (ii) inspect the webpage to find the data from its source code; (iii) build the prototype code, which was written in R language and using the rvest package and intended to extract and prepare the data; (iv) generalize the code considering functions, loops and debugging and run the code alternating among US metropolitan areas; (v) store the data as an organized data frame; (vi) check and clean the gathered data; (vii) geocode the information on each warehouse.…”
Section: Unstructured Web Data Extraction -Warehouse Informationmentioning
confidence: 99%
“…Therefore, we have performed an automated web data extraction method: web scraping. Individual scripts were developed to scrape the warehouse information from the Html file and assemble one dataset for each metropolitan area (Ge et al, 2021;Gharahighehi et al, 2021;Jiao et al, 2021;Luo and He, 2021;Pineda-Jaramillo and Pineda-Jaramillo, 2021;Ploessl et al, 2021). This method was mainly composed of seven steps for this paper: (i) find the URL where the data is published; (ii) inspect the webpage to find the data from its source code; (iii) build the prototype code, which was written in R language and using the rvest package and intended to extract and prepare the data; (iv) generalize the code considering functions, loops and debugging and run the code alternating among US metropolitan areas; (v) store the data as an organized data frame; (vi) check and clean the gathered data; (vii) geocode the information on each warehouse.…”
Section: Unstructured Web Data Extraction -Warehouse Informationmentioning
confidence: 99%
“…These generative probabilistic models primarily concern the derivation of underlying common topics. However, there is limited research that applies topic modelling in the context of real estate market analysis: Ploessl et al (2021) used seeded LDA for the assignment of German news articles to six real estate-related trends and revealed that both the news coverage and sentiment of these expected stable trends show cyclical elements within a 21-year period. Another algorithm, the structural topic model, was used by Koelbl et al (2021) for the detection of risk-factors in the 10-K filings of REITs to investigate how these could affect the risk perceptions of investors.…”
Section: Textual Analysis In Real Estatementioning
confidence: 99%
“…This kind of study is also critical for consolidating emerging research activities and trends as a means for mapping out the direction of knowledge development in the sector. Thus, while real estate research is increasingly gaining momentum, the AfRES has neglected exploring the contributions of academic writings as a body of knowledge and additional source (Nguyen, et al, 2021;Ploessl et al, 2021;. The African Real Estate Society has promoted networking, research, and education among property professionals across Africa and has hosted annual conferences since its formation in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…This study investigates the real estate research trends and directions emerging from the proceedings of AfRES conferences between 2011 and 2022. To achieve this aim, the study answers the following questions: Other similar studies (Breuer and Nadler, 2012;Abatecola et al, 2013;Nguyen et al, 2021;Just et al, 2021) that have looked at research contributions within the International Real Estate Society (IRES) structure have also focused only on the American Real Estate Society, (ARES) and European Real Estate Society (ERES). They note a disproportionate focus on empirical studies within the finance and investment themes.…”
Section: Introductionmentioning
confidence: 99%